2018
DOI: 10.1186/s12885-018-4338-1
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of pathologic stage T3a renal cell carcinoma up-staged from small renal tumor: emphasis on partial nephrectomy

Abstract: BackgroundThe prognosis of patients with pathologic stage T3a renal cell carcinoma (RCC) that is up-staged from a small renal tumor remains controversial. We evaluated the prognosis of patients with RCC who were up-staged from clinical stage T1 to pathologic stage T3a.MethodsWe retrospectively reviewed the data of 3431 patients who were surgically treated for clinical stage T1 RCC. The survival outcomes were compared using Kaplan-Meier and Cox proportional analyses.ResultsAmong the clinical stage T1 patients, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 22 publications
1
34
0
Order By: Relevance
“…In term of follow up time, the median or mean duration period ranged from 23 to more than 60 months. Among the eligible nine studies, seven studies 12-15, 17, 25, 26 containing 10,456 patients were performed to evaluate the impact of pT3a upstaging on the RFS of cT1 RCC patients, six studies (seven cohorts) 12, 15, 24-27 containing 98,884 patients were conducted to investigate the OS and three studies (four cohorts) 12, 24, 26 containing 33,470 patients reported the CSS, respectively. Quality scores of these studies by NOS ranged from 7 to 9, which were considered adequate for the following meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In term of follow up time, the median or mean duration period ranged from 23 to more than 60 months. Among the eligible nine studies, seven studies 12-15, 17, 25, 26 containing 10,456 patients were performed to evaluate the impact of pT3a upstaging on the RFS of cT1 RCC patients, six studies (seven cohorts) 12, 15, 24-27 containing 98,884 patients were conducted to investigate the OS and three studies (four cohorts) 12, 24, 26 containing 33,470 patients reported the CSS, respectively. Quality scores of these studies by NOS ranged from 7 to 9, which were considered adequate for the following meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Some recent studies have focused on the prognostic significance of pT3a upstaging in cT1 RCC undergoing nephrectomy and suggested inconsistent results. Lee et al12 demonstrated that patients with RCC upstaged from clinical stage T1 to pathologic stage T3a showed shorter survival outcomes than those without upstaging. Jeong et al 13 found that pathological T3a upstaging of cT1 RCC was associated with a poor recurrence-free survival, compared with pT1 disease.…”
Section: Introductionmentioning
confidence: 99%
“…The macroscopic and histological features of RCC were assessed, including tumor stage and Fuhrman nuclear grade (26). The tumor stage was defined according to the 2010 TNM classification (48). At presentation, the tumor stage was pT1 in 73, pT2 in 80 and pT3 in 30 cases, and the Fuhrman grade was I in 58, II in 90, III in 29 and IV in 6 umors.…”
Section: Methodsmentioning
confidence: 99%
“…Among these cases, clear cell RCC was the predominant type. Due to the advancements and penetration of modern radiologic imaging techniques, the incidental detection of small renal cell carcinoma (sRCC, ≤4 cm) has been steadily increasing [3].…”
Section: Introductionmentioning
confidence: 99%